Electrochemical formation of palladium islands on HOPG: Kinetics, morphology, and growth mechanisms - Gimeno, Y. (2002)
Scanning tunneling microscopy (STM) and conventional electrochemical techniques were utilized to investigate the growth kinetics and mechanism of palladium island electroformation on highly oriented pyrolitic graphite (HOPG) from aqueous acid palladium chloride solutions at 298 K. Initially, the electrodeposition reaction at low cathodic overpotentials involves an activation process in which a PdCl2 surface intermediate is formed. At intermediate overpotentials, the growth of palladium islands involves a progressive nucleation and growth model under diffusion control, whereas at high overpotentials, the bulk discharge of soluble palladium species undergoes a free convective-diffusion process. As the cathodic overpotential is shifted negatively, the aspect ratio of the islands, defined as the ratio of the maximum height of the island to the island radius, and the island size decrease, whereas the island density increases. As the cathodic overpotential becomes a few millivolts more positive than the threshold potential of the hydrogen evolution reaction, the island shape changes from a compact disk to a quasi-2D dense radial Pd(111) island. The formation of a dense radial morphology and its small departure from a perfect 2D pattern indicates the presence of weak step-edge energy barriers, as expected from theoretical calculations for Pd(111). These results stress the key role of step-edge energy barriers in determining growth patterns during metal electrodeposition.